1997
DOI: 10.1074/jbc.272.46.29068
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Warfarin-sensitive Vitamin K 2,3-Epoxide Reductase Enzyme Complex in the Endoplasmic Reticulum Membrane

Abstract: ␥-Carboxylation of vitamin K-dependent proteins requires a functional vitamin K cycle to produce the active vitamin K cofactor for the ␥-carboxylase which posttranslationally modifies precursors of these proteins to contain ␥-carboxyglutamic acid residues. The warfarinsensitive enzyme vitamin K epoxide reductase (VKOR) of the cycle reduces vitamin K 2,3-epoxide to the active vitamin K hydroquinone cofactor. Because of the importance of warfarin as an anticoagulant in prophylactic medicine and as a poison in ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 39 publications
2
83
0
1
Order By: Relevance
“…The protein resides in the endoplasmic reticulum, and may be complexed with microsomal epoxide hydrolase (encoded by EPHX1), to produce a multiprotein complex that is responsible for vitamin K epoxide reduction. 86,87 Microsomal epoxide hydrolase by itself does not possess vitamin K epoxide reductase activity. 88 Interestingly, a recent study in an Israeli population has shown an association between high doses of warfarin and a coding EPHX1 polymorphism (rs1051740) in CYP2C9 extensive metabolizers.…”
Section: Wadelius and M Pirmohamedmentioning
confidence: 99%
“…The protein resides in the endoplasmic reticulum, and may be complexed with microsomal epoxide hydrolase (encoded by EPHX1), to produce a multiprotein complex that is responsible for vitamin K epoxide reduction. 86,87 Microsomal epoxide hydrolase by itself does not possess vitamin K epoxide reductase activity. 88 Interestingly, a recent study in an Israeli population has shown an association between high doses of warfarin and a coding EPHX1 polymorphism (rs1051740) in CYP2C9 extensive metabolizers.…”
Section: Wadelius and M Pirmohamedmentioning
confidence: 99%
“…43 Since malondialdehyde is the final product of phospholipid peroxidation induced by oxidative stress, the organization of cell membranes in PXE would be different from controls (unpublished data). This, in turn, may affect the activity of enzymes localized on membranes of the endoplasmic reticulum, such as the enzyme g-carboxylase, 44,45 whose activity is necessary for MGP g-carboxylation. Therefore, disturbance of the g-carboxylase system, however induced, might lead to deficient expression of active MGP.…”
Section: Mgp and Elastic Fiber Calcification In Pxe D Gheduzzi Et Almentioning
confidence: 99%
“…Because of our limited knowledge of the vitamin K-dependent ␥-carboxylation system, the mechanism of inhibition is not fully understood (11). However, the recent identification of VKORC1 (12), an 18-kDa ER membrane protein believed to be a subunit of VKOR (13), has provided new opportunities to understand the system. When expressed in various cell lines, VKORC1 increases reduced vitamin K cofactor production (14,15).…”
mentioning
confidence: 99%